Islamic Education Beyond Colonialism: The Development of Muhammadiyah Educational Practices in Bengkulu City Circa 1945-1965 - Novriadi, Dedy; Amnur, Amnah Qurniati; Surohim, Surohim (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
The emergence of Muhammadiyah education in the context of a society under Dutch colonial rule highlights a critical period where access to education was severely restricted due to oppressive colonial policies. This study examines the revitalization efforts in Bengkulu’s post-independence era, focusing on the dynamics and challenges encountered in developing Muhammadiyah’s educational initiatives. It explores how the Muhammadiyah organization navigated and addressed the educational challenges of the time, enabling the community in Bengkulu City to pursue quality education. Employing a historical approach, this research aggregates data from various sources, including key figures and relevant references related to Muhammadiyah education. The findings reveal that the initial phase of Muhammadiyah’s educational development was marked by minimal infrastructure and a shortage of teaching personnel, coupled with the integration of private educational institutions with government schools due to state policies. Through curriculum strengthening and support from the community and government, both morally and spiritually, Muhammadiyah educational institutions emerged as vital forces in combating illiteracy. This study concludes that post-independence Muhammadiyah education played a pivotal role in the intellectual upliftment of the marginalized communities and the organizational development efforts of Muhammadiyah. The implications of this research are significant for the formulation of educational policies, as Muhammadiyah’s educational endeavors are strategically important in achieving excellence in education.